Childhood cancer epidemiology in the Czech Republic (1994–2016). (December 2020) - Krejci, Denisa; Zapletalova, Michaela; Svobodova, Ivana; Bajciova, Viera; Mudry, Peter; Smelhaus, Vratislav; Sterba, Jaroslav; Stary, Jan; Capocaccia, Riccardo; Dusek, Ladislav
Highlights: Childhood cancer mortality decreased between 1994 and 2016 in the Czech Republic. The overall five-year survival increased by 10 %, reaching 85 %. Improvements in survival rates were observed in bone and soft tissues sarcomas. Abstract: Background: The knowledge of cancer burden in the population, its time trends and the possibility of international comparison is an important starting point for cancer control programmes. Our study aimed to evaluate trends in childhood cancer epidemiology of patients aged 0–14 years in the period 1994–2016 in the Czech Republic. Methods: Data on childhood cancers have been obtained from the Czech National Cancer Registry. These data were validated using the clinical database of childhood cancer patients and combined with data from death certificates. Incidence and mortality trends were assessed by the joinpoint regression method. The life tables method was used to calculate the overall age-standardised five-year survival. Results: The incidence trend was stable; the age-standardised (world) cancer incidence – ASR (W) – was 173.7 per 1 million children in the period 1994–2016. However, there was apparent significant decrease in mortality: ASR (W) dropped from 58.1 per 1 million children in 1994 to 21.4 per 1 million children in 2016. The overall five-year survival increased over time by 10 %. Statistically significant improvements in survival were observed in patients with lymphoid leukaemia, astrocytomas, neuroblastomas, osteosarcomas and rhabdomyosarcomas. Conclusion: Such a relevant increase in survival rates, and therefore also a decrease in mortality rates in the Czech Republic, is most likely due to improvements in diagnostic and treatment methods since the 1990s, which were facilitated by the concentration of childhood cancer patients in children's cancer centres.